ANALISIS PERMASALAHAN PEMBELAJARAN DI SD NEGERI CIBIRU 09 KABUPATEN BANDUNG - Alya Malika Fahdini; Yuni Fajariyah; Masrukhatun Najwa Azkia; Alman Musir; Deti Rostika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Problems in learning can come from anywhere, both from situations, students, teachers, and many more complex problems. Therefore, observations were made to identify what learning problems are happening in elementary schools today. The research was conducted by describing data from the field in the form of descriptive paragraphs. In the overall context of education, both teachers and students have their own roles and responsibilities in achieving learning success. By overcoming obstacles, taking solutive steps, and continuing to innovate, education can become more effective and relevant to prepare students for future challenges.